Estudo constrativo de fraseologismos do futebol em corpus jornalístico bidirecional : contribuições para os estudos da tradução em português e espanhol - Alves, Mariama de Lourdes (2017)
Soccer, the most popular collective sport in Brazil and worldwide, has a broad and global format, being considered in spheres that go beyond the rules and players. This is how FIFA (2007) positions itself on this sport, which currently has more than 265 million players, in both men's and women's modalities. More than a sport, soccer is nowadays a theme that influences and relates directly and indirectly to other subjects, having an integrative dimension with the politics, economy and culture of a society. Based on the soccer universe, we measure the importance of such theme in four countries that are passionate about soccer: Argentina, Brazil, Spain and Portugal. These countries, through various factors such as history, championships, world championship and excellent national and international performance of their players, make this sport a favorable environment for research. This research has as main objective the elaboration of a bilingual and contrastive glossary of phraseologies, based on bidirectional, parallel and comparable corpus, in order to collaborate for bilingual studies in Portuguese and Spanish. Furthermore, in this paper we will analyze the data found in the corpus, in particular, how the phraseologies in the soccer field are treated in the journalistic corpora of these languages. The compiled corpus is bi-directional, that is to say, it is in Portuguese and Spanish, it is comparable, for analyzing how phraseologisms are used in the two foreign languages and it is formed by texts of four specific soccer newspapers, the Brazilian newspaper ESPN, the Argentine newspaper OLÉ, The Spanish newspaper SPORT and the Portuguese newspaper RECORD and the newspapers of great circulation El País and Folha de São Paulo. The methodological procedures used in this research consist in the compilation, preparation of the corpus, besides the use of the tools of the program WordSmith Tools - version 6.0 in the specific analyzes of each phraseological unit. Languages are strengthened and enriched by the contact, coexistence and practice of the game, which amplifies the dimensions mentioned above. Seemann (2011), helps us understand the methodological process and also analyze the compiled texts. Besides this work, we highlight the authors Castañón Rodriguez (2014), Matuda (2011) and Rull (2004). To what concerns culture and its relation to the foreign language, we are based on Santos (1985), Brown (1994) and Lopez (2012). In relation to the phraseologisms, we have as main study base the classifications made by Corpas Pastor (1996; 2010). At last, we adopted Berber Sardinha (2004; 2009), Halliday (1991) and Parodi (2010) to support our methodological approach. Through Corpus linguistics, it is possible to perform a systematic analysis of the language, starting from a probabilistic view of the data compiled.